Sulfonylurea induction of caffeine-enhanced insulin secretion and reduction of glycemic levels in diabetic rats. (August 2014) - da Silva, Luiz Augusto; Pereira, Ricardo Aparecido; Túrmina, Janaína Angela; Kerppers, Ivo Ilvan; Osiecki, Raul; Altimari, Leandro Ricardo; Malfatti, Carlos Ricardo Maneck
Abstract Context: Caffeine can stimulate insulin secretion by attenuating hyperglycemia in diabetes models with significant reduction of pancreatic functional β cells. Knowledge of these mechanisms could contribute to new strategies for treating diabetes. Objective: This study evaluated the effects of caffeine and physical exercise on glycemic and insulin responses in diabetic rats. Materials and methods: The diabetes model was induced by intraperitoneal administration of 60 mg/kg of streptozotocin (STZ). Animals were divided into six groups: control, caffeine, STZ control, STZ caffeine, STZ sulfonylurea, and STZ caffeine + sulfonylurea. Acutely, control animals received 6 mg of caffeine and 10 mg/kg sulfonylurea or 10 mg/kg saline. Animals were sacrificed after physical exercise; blood samples were collected for glucose, glycerol, lactate, and insulin analyses. Cardiovascular responses were recorded before and after treatments. A one-way ANOVA and the post hoc Student–Newman–Keuls test were used to analyze statistical differences between treatments (p < 0.05). Results: About 6 mg/kg of caffeine did not alter cardiovascular responses, but promoted blood glucose reduction after 60 min of exercise when compared to animals in the control groups (387–187 mg/dL; p < 0.05). Insulin levels increased significantly (0.6–10 µU/mL; p < 0.05) in rats that received acute caffeine treatment associated with sulfonylurea compared to rats in the other groups. Discussion and conclusion: Acute caffeine intake with exercise can increase glucose uptake enhancing insulin secretion stimulated by sulfonylurea in β cells-deficient pancreas. The results indicate the potential use of caffeine as a strategy for glycemic and insulin control in diabetes.